Answer:
x =
![(p)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1uuxhln8ywg7m4qemntydojzezic08ny2w.png)
Explanation:
x ∝ p
x = kp -------(1)
Where k is the constant of proportionality.
Now, x = 2 when p = 4
Putting in the above formula
2 = k(4)
Dividing both sides by 4
k =
![(2)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kgo1kuoy78ddfogdtx73wzxweq7p5h4xyh.png)
=> k =
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
Putting k in (1)
x =
![(p)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1uuxhln8ywg7m4qemntydojzezic08ny2w.png)
Now this is the required equation connecting both.